2008
DOI: 10.1080/15389580701670705
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Two Training Approaches to Improve Older Adults' Driving Safety

Abstract: The results of this study demonstrate that education programs focused on the needs of older drivers may help improve their knowledge of safe driving practices and actual driving performance. Further research is required to determine if these changes will affect other variables such as driver confidence and crash rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 37 publications
5
79
0
Order By: Relevance
“…Similarly, Bédard and colleagues (2004), examined a widely-used educational intervention and found that the training did not result in significant improvements during an on-road evaluation. There is some evidence that educational programs combined with other components, such as on-road training (Marottoli et al, 2007b;Bédard et al, 2008) may improve onroad driving.…”
Section: Approaches To Preventionmentioning
confidence: 99%
“…Similarly, Bédard and colleagues (2004), examined a widely-used educational intervention and found that the training did not result in significant improvements during an on-road evaluation. There is some evidence that educational programs combined with other components, such as on-road training (Marottoli et al, 2007b;Bédard et al, 2008) may improve onroad driving.…”
Section: Approaches To Preventionmentioning
confidence: 99%
“…Control of lane position is one aspect of driving which is not captured adequately by observational measures of driving behaviour: it is often scored using a scale ranging from "good" to "bad" Akinwuntan, De Weerdt, et al, 2005) or via the accumulation of violation points scored by the examiner (Bédard et al, 2008). Such measures may capture extreme errors in position (i.e.…”
Section: Steering Controlmentioning
confidence: 99%
“…Crashes and missed stops (ie., a participant failed to stop before an intersection, which includes overshoots by a few feet) were recorded by the STISIM drive software. The experimenter also assessed drivers' simulator performance (G2-rater) using the evaluation procedure employed by Bédard et al (2008).…”
Section: Driving Performance Measurementioning
confidence: 99%